(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A cross sectional study was conducted in rural areas of Kibaha district within the Coastal region of Tanzania to assess knowledge on dosage, storage, expiry and dispensing practices of antimalarial drugs among households, drug stores and ordinary shops. A standard questionnaire was administered to 253 household members to assess their knowledge as regards storage, sources and use of antimalarial drugs. Drug sellers in 20 drug stores and 39 shopkeepers in ordinary retail shops were also interviewed and their dispensing practices of antimalarials and other over the counter drugs were observed and recorded. The results showed that 35 % of household members interviewed knew the dates and importance of drug expiry, whereas 65 % kept drugs without knowing expiry dates. Only 16 % of household members were informed of the expiry dates of drugs at the facilities they attended. Furthermore, 48 % of these household members could state three or more symptoms of malaria correctly. The majority of drug store (53 %) and ordinary retail shop (75 %) sellers did not dispense correct doses of antimalarials due to low literacy and lack of dosage guidelines or package inserts. In order to reduce incidences of drug poisoning due to over-dosage or drug resistance due to under dosage, there is need to educate both consumers and dispensers on correct dosage regimens through mass media such as radio, health education programs, television, posters, leaflets and newspapers.